Plan the territory from the landscape: The case of the city of La Plata (ARQUISUR Revista, 2019)
To approach this research, we start by understanding the landscape as the result of the interaction between man and nature. It is proposed to carry out an analysis on the formal structure of the landscape in Gran La Plata, understanding the landscape as a key factor for territorial planning. The methodology adopted is based on a first diagnostic of the region to identify the different types of land uses and the urban  ​​expansion area in the last three decades. In a second instance, a synthesis of the urban-territorial diagnosis will be elaborated and the types of landscape identified in the study area will be determined, allowing in this way to elaborate a landscape diagnosis that contemplates the problem of the urban expantion area. Finally, a third stage is developed that includes strategies and guidelines that would position the study area more efficiently in the face of the new growth trends that demand a more sustainable urban development for cities. In this sense, knowledge about the landscape must point to action, to stop the loss of identity and landscape quality, focusing on identifying and promoting the values ​​and characteristics of the landscape from an interdisciplinary perspective.
Keywords: city; development strategy; landscape; urban planning; land use